The Impact of Methane on Microbial Communities at Marine Arctic Gas Hydrate Bearing Sediment - Carrier, Vincent; Svenning, Mette M.; Gründger, Friederike; Niemann, Helge; Dessandier, Pierre-Antoine; Panieri, Giuliana; Kalenitchenko, Dimitri (Frontiers in Microbiology, 2020)
Cold seeps are characterized by high biomass, which is supported by the microbial oxidation of the available methane by capable microorganisms. The carbon is subsequently transferred to higher trophic levels. South of Svalbard, five geological mounds shaped by the formation of methane gas hydrates, have been recently located. Methane gas seeping activity has been observed on four of them, and flares were primarily concentrated at their summits. At three of these mounds, and along a distance gradient from their summit to their outskirt, we investigated the eukaryotic and prokaryotic biodiversity by using specific primers targeting the 16S and 18S rDNA. Here we show that local methane seepage and other environmental conditions did affect the microbial community structure and composition. We could not demonstrate a community gradient from the summit to the edge of the mounds. Instead, a similar community structure in any methane-rich sediments could be retrieved at any location on these mounds. The oxidation of methane was largely driven by ANME-1 and the communities also hosted high relative abundances of sulphate reducing bacterial groups although none demonstrated a clear co-occurrence with the predominance of ANME-1. Additional common taxa were observed and their abundances were likely benefiting from the end products of methane oxidation. Among these were sulphide oxidizing Campilobacterota, organic matter degraders, such as Bathyarchaeota, Woesearchaeota or thermoplasmatales MBG-D, and heterotrophic ciliates and Cercozoa.